1968
DOI: 10.1037/h0026737
|View full text |Cite
|
Sign up to set email alerts
|

Motivational effects of knowledge of results: A goal-setting phenomenon?

Abstract: Hypothesized that the motivational effects of knowledge of results (KR) were a function of the goals Ss set in response to such knowledge. Previous studies were classified into 4 categories according to the degree to which KR and goal setting effects were separated: (1) 1 group of studies explicitly confounded the 2 variables by assigning KR and no-KR Ss different goals; (2) other studies gave KR only in relation to standards or gave S a record of his previous performance, both of which procedures probably enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
1
2

Year Published

1973
1973
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 232 publications
(92 citation statements)
references
References 39 publications
1
88
1
2
Order By: Relevance
“…Earlier research on the relationship of goal setting and task performance found that when goal setting was controlled, providing subjects with knowledge of their scores on a task did not motivate better performance than giving them no knowledge of their scores (Locke, 1967;Locke & Bryan, 1969;Locke, Cartledge & Koeppel, 1968). These studies indicated that feedback alone was not sufficient to increase task motivation.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Earlier research on the relationship of goal setting and task performance found that when goal setting was controlled, providing subjects with knowledge of their scores on a task did not motivate better performance than giving them no knowledge of their scores (Locke, 1967;Locke & Bryan, 1969;Locke, Cartledge & Koeppel, 1968). These studies indicated that feedback alone was not sufficient to increase task motivation.…”
mentioning
confidence: 78%
“…Locke (1968) has argued that competition may affect performance by affecting the level at which goals are set and/or the degree of commitment to these goals.…”
Section: Discussionmentioning
confidence: 99%
“…Performance feedback is widely recognized as an essential condition for motivation and for learning in organizational as well as other settings (Adams, 1968;Ammons, 1956;Annett, 1969;Bilodeau, 1966;Locke, Cartledege, and Koeppel, 1968;Sassenrath, 1975). Yet, in spite of the large and varied literature, generalizations which can be applied to organizational settings are difficult to obtain.…”
Section: Effects Of Performance Feedback In Organizational Settingsmentioning
confidence: 99%
“…This assumption is prevalent especially in research ou knowlege-of-results. Typically, an individtl is told that his or her performance is at a given level and it is assumed that this information is perceived as communicated (Baller, 1970;Chapanis, 1964;Cummings, Schwab, and Rozen, 1971;Gibbs and Braun, 1965;Locke, 1967;Locke et al, 1968). Although such an assumption is quite reasonable in the types of laboratory research typically employed to test knowledge of results effects (e.g., Locke, 1967), in performance settings with employees or students in on-going organizations, the assumption is much less acceptable.…”
Section: Ia5mentioning
confidence: 99%
“…Kanfer (1971) has supported knowledge of results as a reward, basing his argument on the work of Locke, Cartledge, and Koeppel (1968), who have indicated that knowledge of results influences behavior, goal setting, and standards of evaluation. Kanfer (1970) has supported the use of ambiguous stimuli in labora tory studies of self-reward, claiming that self-reward occurs most frequently in the environment following ambiguous stimuli which re quire the person to subjectively judge the adequacy of his or her own response.…”
Section: Methodological Considerations In Laboratory Studies Of Self-mentioning
confidence: 99%